Las estrategias de comunicación institucional del Gobierno Autónomo Descentralizado Municipal del cantón Loja y la participación ciudadana en la obra pública municipal. período marzo-julio de 2015 - González Loaiza, Pedro Xavier (2016)
The development of this research work arises from the need to know what way corporate communication strategies Decentralized Autonomous Municipal Government of Canton Loja disseminate and encourage the participation of citizens in urban parishes in Loja in municipal public works? Ecuador's Constitution and other laws derived from it, have that public participation should be promoted by local self-government as it is a right of everyone involved in public affairs to assist the development of the community in which they live. According to a preliminary investigation it was learned that there is no precedent of a study analyzing how the communication that influence participation within the municipal GAD. After this has been observed that there is a specific job in corporate communication by the municipal GAD Loja to facilitate the implementation of citizen participation in the institution. It could also see in the media, that being a political issue, participation has been used excessively to generate political opposition, which seems to be hindering the free fulfillment of this right. Justifications were made, in all its aspects and literature review issues settled that allowed a bibliographic support to develop the present study. Tools such as observation, surveys and interviews to collect information were used. It was concluded that the Municipal GAD of Loja has strategies limited communication, because given the results of the surveys and observation, lack disseminate, promote and greater openness to people in the knowledge and use of citizen participation ways institution. La performing all the research work was based on a schedule of activities and material, intellectual and financial resources that enabled the successful completion of the research work